Industry Transformation via Channel Disruption. Issue 1 (3rd April 2017) - Crittenden, Andrew B.; Crittenden, Victoria L.; Crittenden, William F.
Abstract : We are living in an era of disruption. Massive changes are affecting businesses and these changes are impacting traditional channels of distribution. Industries are evolving with many reaching maturity and searching for ways to create growth. Although incumbents seek to survive, this new era has created vast opportunities for startups to shake-up the status quo. This shake-up is appearing in the exchange occurring between customers and companies with the exchange facilitated by the channel of distribution. The intent of this article is to describe rapid changes occurring in a small number of industries (i.e., financial services, real estate, healthcare, and transportation) in the hopes of creating excitement for future scholarly exploration related to channels of distribution in the sharing economy.